2014
DOI: 10.3109/08820538.2014.959189
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Surgery in Pseudoexfoliation Syndrome

Abstract: Pseudoexfoliation (PXF) syndrome is characterized by the deposition of distinctive fibrillar material in the anterior segment of the eye. It is an age-related process that is associated with open and narrow angle glaucomas and the formation of cataracts. Not only is PXF associated with the formation of dense nuclear cataracts, it is also well known that those presenting with PXF are at a higher risk of developing complications during, and even after, cataract surgery. Complications associated with cataract sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 41 publications
1
32
0
7
Order By: Relevance
“…In exfoliation syndrome, for example, the zonular fibers are weakened, resulting in phacodonesis and subluxation of the lens, or even frank zonulysis. 19 , 20 Systemic metabolic disorders, such as homocystinuria, commonly result in lens dislocation (ectopia lentis) secondary to disintegration of zonular fibers. In isolation, ectopia lentis is associated with mutations in ADAMTSL-4, 21 , 22 but is also observed in syndromes resulting from mutations in genes such as FBN1 (Marfan syndrome; MIM:154700) and LTBP2 (Weill-Marchesani syndrome type 3; MIM:614819).…”
mentioning
confidence: 99%
“…In exfoliation syndrome, for example, the zonular fibers are weakened, resulting in phacodonesis and subluxation of the lens, or even frank zonulysis. 19 , 20 Systemic metabolic disorders, such as homocystinuria, commonly result in lens dislocation (ectopia lentis) secondary to disintegration of zonular fibers. In isolation, ectopia lentis is associated with mutations in ADAMTSL-4, 21 , 22 but is also observed in syndromes resulting from mutations in genes such as FBN1 (Marfan syndrome; MIM:154700) and LTBP2 (Weill-Marchesani syndrome type 3; MIM:614819).…”
mentioning
confidence: 99%
“…Cataract surgery in case of weak zonules is more challenging and time consuming and has a higher risk of intraoperative and postoperative complications than ordinary cataract cases [2,3,8,11]. Phacoemulsification with capsular stabilizing devices is a more preferred surgical method than extracapsular or intracapsular cataract extraction and pars plana lensectomy combined with vitrectomy [4,5,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoexfoliation syndrome is associated with multiple ocular manifestations, including weak zonules [1]. If cataract surgery is necessary in such a case, it might be challenging for surgeons to perform the surgery [2,3]. To improve surgical outcome and long-term prognosis, different devices for weak zonule management have been introduced such as conventional and modified capsular tension rings (CTRs) and iris and capsular hooks [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Cataract surgery is a necessary method to increase vision in patients with low vision due to cataract (20,21). In pseudoexfoliation cases, cataract causes a decrease in vision and surgical intervention is necessary to increase vision (22,23). Many studies have shown that pupillary dilatation in eyes with pseudoexfoliation is insufficient (24,25).…”
Section: Discussionmentioning
confidence: 99%